Imaging structure and function - Jbabdi, S (Elsevier, 2009)
Modern neuroimaging techniques provide us with a unique window into studying both structure and function of living brains. The increasing quality and resolution of structural brain images is starting to reach the frontiers of in vivo histology. Advances in methods and modeling allow structural measurements to become more quantitative, and provide both automated and accurate brain morphometry. On the other hand, functional neuroimaging now provides a large spectrum of devices and methods for measuring brain activity either directly (electro-magnetic recordings) or indirectly via hemodynamic effects. Magnetic resonance imaging (MRI) has proven to be particularly well suited for obtaining detailed pictures of various brain structures. MRI has particular advantages in that it is non-invasive, uses non-ionizing radiation (compared to e.g. X-rays), and has a high soft-tissue resolution and discrimination. It also provides both morphological and functional information. Combining structural and functional imaging data generally provides a far richer picture of the anatomical substrate of observed function, and enhances in many cases the interpretation of the results obtained using either data alone. Structural MRI supplies information on brain morphology, both in gray and white matter, and can potentially provide measures of the tissue microstructure. Diffusion-weighted MRI plays a unique role in this context, giving us insight into brain networks, in terms of both their connectional diagram and microstructural features, and can be explicitly related to both brain function and behavior. © 2009 Copyright © 2009 Elsevier Inc. All rights reserved.